2016
DOI: 10.1007/s10943-016-0271-2
|View full text |Cite
|
Sign up to set email alerts
|

Unbelievable?! Theistic/Epistemological Viewpoint Affects Religion–Health Relationship

Abstract: Research suggests that Religion/Spirituality promotes a variety of positive health outcomes. However, despite reporting lower levels of Religion/Spirituality, non-believers report comparable levels of health to believers. The current study tested the hypothesis that Religion/Spirituality does not have a uniform effect on health for all persons, and tested theological/epistemological categories as moderators. Using the 2012 and 2014 General Social Survey (N = 2670), the relationship between Religion/Spiritualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…Our findings suggest that atheists/theists and the religiously unaffiliated/ affiliated do not systematically differ with regard to fatalism and nihilism, constructs that are routinely linked with psychological well-being. Overall, these findings would be consistent with at least a few other studies that find that atheists or the religiously unaffiliated do not suffer from psychological deficits because of their position (Galen & Kloet, 2011;Speed, 2017).…”
Section: Are the Irreligious More Likely To Be Fatalists And Nihilists?supporting
confidence: 90%
See 2 more Smart Citations
“…Our findings suggest that atheists/theists and the religiously unaffiliated/ affiliated do not systematically differ with regard to fatalism and nihilism, constructs that are routinely linked with psychological well-being. Overall, these findings would be consistent with at least a few other studies that find that atheists or the religiously unaffiliated do not suffer from psychological deficits because of their position (Galen & Kloet, 2011;Speed, 2017).…”
Section: Are the Irreligious More Likely To Be Fatalists And Nihilists?supporting
confidence: 90%
“…However, other research has shown that the irreligious do not experience deficits in meaning in life (Caldwell-Harris et al, 2011;Wilkinson & Coleman, 2010), happiness (Speed, 2017;, or well-being (Galen, 2015;Streib & Klein, 2013), and that the irreligious do not differ in terms of psychological well-being (Galen, 2015;Streib & Klein, 2013;although cf. Hayward, Krause, Ironson, Hill, & Emmons, 2016).…”
Section: Nonreligion and Meaning In Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Studies looking at affiliation have often found that being nonaffiliated is not associated with self‐reported measures of health . Studies that differentiated between different types of nonaffiliation (atheists, agnostics, nonreligious, etc) found that these effects are complex, often with some nonaffiliated groups having better health outcomes than other nonaffiliates and the religiously affiliated …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous studies have been conducted on the relationship between religion and mental health. These studies have generally shown that there is a positive relationship between religion and health (Speed, ,2017). But in some studies, vague and inaudible connection has been reported between various aspects of religiosity and psychological compilation.…”
Section: Introductionmentioning
confidence: 99%